The Effect of Stress on the Occurance of Dysmenorrhea - Nurlailis Saadah; Hanif Azizah; Rahayu Sumaningsih; Heru Santoso Wahito Nugroho (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Adolescence is a period of “storm and stress”, a time when emotional tension increases due to physical and glandular changes that make adolescents very sensitive and prone to stress. Stress management is also one of the efforts to overcome dysmenorrhea because stress factors can reduce a person's pain resistance. This study aims to determine the effect of stress on the incidence of dysmenorrhea. This study was an observational analytic study using a cross-sectional approach. The study population was seventh and eighth grade students of Junior High School Ngariboyo, totaling 179 female students. Sampling using the Slovin sample size formula, samples were taken using simple random sampling technique with a minimum sample size of 124 female students. The independent variable was stress, while the dependent variable was dysmenorrhea. Data were collected using the Depression Anxiety Stress Scale (DASS-42) questionnaire, and the Numerical Rating Scale (NRS). Data were processed and analyzed using Ordinal Regression test. The results showed that there were 49 female students who had moderate stress and 53 female students who experienced moderate dysmenorrhea pain. The results of the Ordinal Regression test showed the effect of stress on the occurance of dysmenorrhea p-value = 0.017. Based on the description above, it can be concluded that there is a significant influence between stress and the incidence of dysmenorrhea in seventh and eighth grade students of Junior High School Ngariboyo. It is expected that female students can increase their knowledge in managing themselves early on in stress management towards the occurance of dysmenorrhea.